ANALISIS FAKTOR YANG MEMENGARUHI PERILAKU MANAJEMEN KEUANGAN DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL INTERVENING PADA ASN RSUD dr. H. KOESNADI BONDOWOSO - Arfandi, Achmad; Karnadi, Karnadi; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Managing finances is very important for everyone; someone must manage well to balance income and expenses, meet life's needs and avoid getting caught in financial difficulties. This study aimed to analyze the role of locus of control in mediating financial knowledge and financial attitudes towards the financial management behaviour of ASN RSUD dr. H. Koesnadi Bondowoso. The population in this study were the State Civil Apparatus (ASN) of RSUD dr. H. Koesnadi Bondowoso. The sampling technique was determined by purposive sampling. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM. The results of the direct effect hypothesis test using the Smart PLS 4.0 application show that financial knowledge has a significant positive effect on the locus of control, financial attitudes have a significant positive effect on the locus of control, financial knowledge has a significant positive effect on financial management behaviour, financial attitudes have a significant positive effect on financial management behaviour, locus of control has a positive but insignificant effect on financial management behaviour, financial knowledge on financial management behaviour through locus of control has a positive but insignificant effect, financial attitudes on financial management behaviour through locus of control has a positive but insignificant effect.